External Balance in Low Income Countries - Christiansen, Lone Engbo (IMF Working Papers; Working Paper ;, 2009)
This paper offers a coherent empirical analysis of the determinants of the real exchange rate, the current account, and the net foreign assets position in low income countries. The paper focuses on indicators specific to low income countries, such as the quality of policies and institutions, the special access to official external financing, and the role of shocks. In addition to more standard factors, we find that domestic financial liberalization is associated with higher current account balances and net foreign asset positions, while capital account liberalization is associated with lower current account balances and net foreign asset positions and with more appreciated real exchange rates. Negative exogenous shocks tend to raise (reduce) the current account in countries with closed (opened) capital accounts. Finally, foreign aid is progressively absorbed over time through net imports, and is associated with a more depreciated real exchange rate in the long-run.